2014
DOI: 10.1371/journal.pone.0087659
|View full text |Cite
|
Sign up to set email alerts
|

The Calpain Inhibitor MDL28170 Induces the Expression of Apoptotic Markers in Leishmania amazonensis Promastigotes

Abstract: BackgroundHuman cutaneous leishmaniasis is caused by distinct species, including Leishmania amazonensis. Treatment of cutaneous leishmaniasis is far from satisfactory due to increases in drug resistance and relapses, and toxicity of compounds to the host. As a consequence for this situation, the development of new leishmanicidal drugs and the search of new targets in the parasite biology are important goals.Methodology/Principal FindingsIn this study, we investigated the mechanism of death pathway induced by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 55 publications
(92 reference statements)
1
23
0
Order By: Relevance
“…However, other phospholipid classes which participate in apoptosis, like phosphatidylethanol sphingomyelin and phosphatidyl choline, can also enable annexin V staining, and therefore annexin V binding is used as an early indicator of apoptosis by many other investigators (35,50). Our results of annexin V-FITC and PI indicated necrosis as shift from the UR to the UL quadrant of synthesized-Ag NP-treated parasites.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…However, other phospholipid classes which participate in apoptosis, like phosphatidylethanol sphingomyelin and phosphatidyl choline, can also enable annexin V staining, and therefore annexin V binding is used as an early indicator of apoptosis by many other investigators (35,50). Our results of annexin V-FITC and PI indicated necrosis as shift from the UR to the UL quadrant of synthesized-Ag NP-treated parasites.…”
Section: Discussionmentioning
confidence: 60%
“…The histogram and images are representative of three independent experiments. A total of 10,000 events from each sample were acquired to ensure adequate data (35).…”
Section: Analysis Of Externalized Phosphatidylserinementioning
confidence: 99%
“…Depolarization of mitochondria transmembrane potential ( Δψm ) is an initial biochemical facet implying activation of the intrinsic apoptotic pathway, as the initial triggering signal of apoptosis (Marinho et al, 2014). In addition, it has been proven to be an important feature for cell death in protozoa parasites such as Leishmania (Sen et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Further studies showed that MDL28170 was able to inhibit the interaction of trypomastigotes with macrophages and intracellular survival [ 28 ], besides interfering in the parasite adhesion to the insect midgut and in the differentiation process of epimastigotes into metacyclic trypomastigotes [ 18 ]. Interestingly, in L. amazonensis , MDL28170 was also shown to induce the expression of apoptotic markers [ 29 ].…”
Section: Resultsmentioning
confidence: 99%